Pengaruh Substitusi Tepung Kacang Tunggak (Vigna unguiculata) Pada Pembuatan Chiffon Cake Terhadap Sifat Fisik dan Daya Terima Konsumen - Asnawi, Zavira; S, I Gusti Ayu Ngurah; Sachriani, Sachriani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the influence of the percentage substitution of cowpea flour (Vigna unguiculata) in making chiffon cake on the physical properties in the aspects of growth power and bake loss as well as consumer acceptability with hedonic tests which including aspects of top crust color, side crust color, crumb color, aroma, sweetness, cowpea taste, texture, and pores. This research was conducted in the pastry and bakery laboratory of the Culinary Education Study Program, Faculty of Engineering, Jakarta State University which lasted from October 2022 to January 2024. This research is included in quantitative research which uses experimental methods for 3 treatments (substitution 30%, 40% and 50%). Based on the results of measuring physical properties using the Anova test, it shows that there is an influence on the growth power and bake loss aspects, so it is continued with the Duncan Multiple Range Test. So that the chiffon cake substituted with cowpea flour 30% significantly different with a growth power of 73.42%, while the chiffon cake substituted with cowpea flour 50% significantly different with a bake loss of 19.50%. The results of hedonic test measurements using statistical hypothesis testing with the Friedman test show that there is no influence of cowpea flour substitution on consumer acceptability in all aspects including top crust color, side crust color, crumb color, aroma, sweetness, cowpea taste, texture and pores, so it did not continue with further tests. Based on the results of the Friedman test, there are 5 out of 8 aspects at 40% substitution including top crust color, side crust color, crumb color, aroma and cowpea taste that consumers like. So, it can be concluded that chiffon cake substituted with cowpea flour with a percentage of 40% is the most preferred formula